2000
DOI: 10.1152/ajprenal.2000.279.4.f755
|View full text |Cite
|
Sign up to set email alerts
|

EP1and EP4receptors mediate prostaglandin E2actions in the microcirculation of rat kidney

Abstract: Vasodilator prostaglandin PGE(2) protects the kidney from excessive vasoconstriction during contraction of extracellular fluid volume and pathophysiological states. However, it is not yet clear which of the four known E-prostanoid (EP) receptors is localized to resistance vessels and mediates net vasodilation. In the present study, we assessed the presence, signal transduction, and actions of EP receptor subtypes in preglomerular arterioles of Sprague-Dawley rat kidneys. RNA encoding EP(1), an EP(1)-variant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 38 publications
6
69
1
Order By: Relevance
“…In this study, we revealed the expression of the EP1 message within the glomeruli, mostly in the mesangial area, by in situ hybridization ( Figure 5), but its expression in renal microvessels was not apparent. Recently, it has been shown that the EP1 receptor is expressed in isolated preglomerular microvessels in rats by RT-PCR (34). Moreover, a recent report on immunohistochemical localization of EP receptors in human kidney revealed that the EP1 receptor is present in renal microvessels, including afferent and efferent arterioles (35).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we revealed the expression of the EP1 message within the glomeruli, mostly in the mesangial area, by in situ hybridization ( Figure 5), but its expression in renal microvessels was not apparent. Recently, it has been shown that the EP1 receptor is expressed in isolated preglomerular microvessels in rats by RT-PCR (34). Moreover, a recent report on immunohistochemical localization of EP receptors in human kidney revealed that the EP1 receptor is present in renal microvessels, including afferent and efferent arterioles (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether EP 1 on afferent arteriole smooth muscle cells really conveys proliferative signals remains to be determined, since vascular smooth muscle cells from arterioles no longer express EP 1 after cell culture, making the in vitro analysis difficult. 14 Furthermore, we could not determine whether EP 1 mRNA expression in the afferent arterioles differs between WKY and SHRSP, since EP 1 gene expression level in afferent arterioles was not high enough for detection by in situ hybridization. Using microdissection and RT-PCR, Purdy et al 14 reported that EP 1 expression can be detected in freshly isolated rat afferent arterioles.…”
Section: Suganami Et Al Significance Of Ep 1 In Malignant Hypertensionmentioning
confidence: 98%
“…14 Furthermore, we could not determine whether EP 1 mRNA expression in the afferent arterioles differs between WKY and SHRSP, since EP 1 gene expression level in afferent arterioles was not high enough for detection by in situ hybridization. Using microdissection and RT-PCR, Purdy et al 14 reported that EP 1 expression can be detected in freshly isolated rat afferent arterioles. The present study also showed that perivascular and interstitial fibrosis together with upregulation of TGF-␤ was attenuated by EP 1 A treatment.…”
Section: Suganami Et Al Significance Of Ep 1 In Malignant Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…All EP receptor types are expressed within the kidney in humans (19) and rodents (20). It has been shown that PGE 2 is involved in the regulation of renal blood flow, electrolyte and water reabsorption, and GFR, most likely by interaction with distinct EP receptor subtypes with specific tubular and vascular localization (19,(21)(22)(23)(24)(25)(26)(27). One may speculate that the detrimental effect of PGE 2 in patients with HPS/aBS is a consequence of enhanced blood flow or glomerular filtration, reduced electrolyte reabsorption in the distal tubule, or inhibition of arginine vasopressin-stimulated water reabsorption, which suggests an important and combined role for EP1, EP2, EP3, and EP4 receptor activation.…”
mentioning
confidence: 99%